IMPLEMENTATION OF GRATITUDE IN PROSOCIAL BEHAVIOR (Research on Volunteer of Ketimbang Ngemis Bandung Community) - Sari Puteri Deta Larasati; Mulyana Mulyana; Naan Naan (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2020)
This reaserch is based on the background that gratitude is not only able to give meaning to someone, but also can encourage individuals to be more sensitive and direct their gratitude to the surrounding environment. This study besides aiming to find out how the meaning of gratitude and prosocial behavior carried out by Ketimbang Ngemis Bandung volunteers, in order to find out whether they implemented the gratitude to the right person or not. This research method uses descriptive qualitative analysis, which describes or tells the atmosphere of time, place, and events, which occur in the field as it is without any manipulation, this type of research uses a theoretical basis to be used as a guide to match the facts in field. The results of this study reveal that the Ketimbang Ngemis Bandung volunteers can recognize and appreciate all gifts received from outside themselves, such as always grateful and those who have helped them. It can be seen from those who have their own stories that give rise to gratitude who wish to do something for the good that they have got. In addition they are able to reflect their gratitude in the form of altruistic, such as conducting donation activities, namely by conducting a survey stage one, surveys stage two, and execution, so that donations can be distributed to the right people.